KRITIK SOSIAL PADA NASKAH DRAMA MONOLOG â€œTOLONGâ€ KARYA NANO RIANTIARNO - Aliyah, Himatun; Sabila, Rapika; Fatmawati, Lita (Magistra Andalusia: Jurnal Ilmu Sastra, 2023)
Using a literary sociology approach, this study aims to describe the various forms of social criticism contained in Nano Riantiarno's monologue Please. Descriptive method is used in this qualitative research. Swingewood's sociology of literature is used in the study of social criticism in the research conducted. Data analysis methods used include content analysis and descriptive analysis. The data source for this research is the manuscript of the monologue Please by Nano Riantiarno, and the data is in the form of excerpts from the text. According to the results and discussion of this study, there are four social criticisms in Nano Riantiarno's monologue drama script Please: 1) Social Criticism of Poverty Issues; 2) Social Criticism of Crime Problems; 3) Social Criticism of Family Disorganization Issues; and 4) Social Criticism of Bureaucratic Problems.